Lawfulness, Legitimacy, and the Limits of Discretionary Power in Democratic Governance - Andreescu, Marius (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
The governance of a democratic state is underpinned by the intricate and symbiotic relationship between Constitutional and Administrative Law. These legal frameworks collectively shape the mechanisms through which state power is exercised, ensuring that the administration of government is both effective and aligned with the fundamental principles of democracy. The coding is not only the expression of the political will of the lawmaker, but it is a complex juridical technique for the choosing and systematisation of the normative content necessary and adequate to certain social, political, economic, and institutional realities. Since the Constitution is a law, yet it nevertheless distinguishes itself from the law, the problem is to establish which juridical norms it contains. The solution to this problem needs to consider the specifics of the fundamental law and also of the requirements of the coding theory. The determination with all scientific stringency of the normative content of the Constitution is indispensable both for the removal of any inaccuracy in delimiting the differences from the law, for the stability and predictability of the fundamental law and last, but not least, for the reality and effectiveness of its supremacy. In our study, an analysis was conducted based on the comparison of the criteria of the techniques and exigencies for the choosing and systematisation of the constitutional norms with reference to their specific, to the practice of other states and within a historical context. The analysis is aimed at the actual proposals for revising the Constitution. In conclusion, Strengthening the judiciary power, the control of the courts and control of constitutionality, particularly, mainly in situations where being questioned the violation of human rights or the principles of lawful state, particularly the separation and balance of powers, can be a viable solution to ensure not only the legality of the measures taken by the state authorities, but also of their legitimacy.